2016
DOI: 10.20960/nh.93
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensión en relación con estado nutricional, actividad física y etnicidad en niños chilenos entre 6 y 13 años de edad

Abstract: Introducción: obesidad e inactividad física son importantes factores de riesgo para el desarrollo de hipertensión en adultos. No obstante, hay poca evidencia sobre el efecto de estos factores de riesgo en el desarrollo de hipertensión en población infantil. Objetivo: investigar la asociación del estado nutricional, niveles de actividad física y etnicidad con niveles de hipertensión en escolares entre 6 y 13 años de edad. Métodos: un total de 418 escolares de ascendencia étnica europea (n = 311) y mapuche (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…From a total of 604 potentially eligible participants, 540 children who met all the inclusion criteria were formally enrolled in the study (Figure ). To classify the ancestry of the schoolchildren, we used the two family surnames of the participants relating to a first degree of Mapuche or European or a second familial degree of Mapuche or European, similar to previous studies (Álvarez et al, ; Morgan, Wei, & Virnig, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a total of 604 potentially eligible participants, 540 children who met all the inclusion criteria were formally enrolled in the study (Figure ). To classify the ancestry of the schoolchildren, we used the two family surnames of the participants relating to a first degree of Mapuche or European or a second familial degree of Mapuche or European, similar to previous studies (Álvarez et al, ; Morgan, Wei, & Virnig, ).…”
Section: Methodsmentioning
confidence: 99%
“…Childhood hypertension has been associated both with genetic (Wang et al, ) and numerous environmental factors, including physical inactivity, fast food (Kar & Khandelwal, ), high salt consumption (Campanozzi et al, ), long screen time (Lissak, ), artificial light (Touitou, Reinberg, & Touitou, ), and is highly related with obesity. A previous study cohort showed differences in both obesity (19.1% and 12.2%) and hypertension (18.6% and 28.9%) prevalence between European and Mapuche schoolchildren (Álvarez et al, ). Additionally, governmental reports about schoolchildren from the Ministry of Education of Chile have recently described a prevalence of similar characteristics (24.6%) in relation to obesity but did not consider ethnic differences (MINEDUC, ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Así mismo, algunas investigaciones han relacionado el estado nutricional durante la infancia con el desarrollo de enfermedades crónico-degenerativas en etapa adulta. En Chile se encontró que la prevalencia de hipertensión arterial presentó una tendencia significativa a aumentar con el incremento del índice de masa corporal (24) .…”
Section: Normalunclassified
“…Among schoolchildren, obesity and its related metabolic consequences (i.e. poor glucose control attributable to increased insulin resistance [IR]) and a low muscle performance are a serious health problem . The World Health Organization recommends 60 min/day of physical activity to maintain children's health .…”
Section: Introductionmentioning
confidence: 99%